Ethical Foundations Of Islamic Economics: A Critical Review Of Contemporary Development Models - Moh. Dimas Adi Putra (PT. Samudra Solusi Profesional, 2026)
Contemporary development models grounded in mainstream economics have demonstrated persistent limitations in addressing structural inequality, financial instability, and the erosion of social cohesion. These shortcomings have reinvigorated scholarly interest in value-based economic frameworks, among which Islamic economics occupies a distinctive and increasingly prominent position. Rooted in the ethical imperatives of the Quran and Sunnah, Islamic economics offers a normative architecture that embeds moral accountability, distributive justice, and comprehensive human well-being within economic theory and practice. This study presents a critical review of the ethical foundations of Islamic economics, examining how its core principles, including the prohibition of riba (interest), the imperative of adl (justice), the concept of maslahah (public interest), and the Maqashid al-Shariah framework, engage with and critique contemporary development models. Drawing on peer-reviewed literature, institutional reports, and foundational theoretical works published between 2015 and 2024, the review identifies four major thematic areas: (1) the epistemological and normative divergence between Islamic and mainstream economics; (2) the ethical critique of interest-based financial systems; (3) the Maqashid al-Shariah as a multidimensional development philosophy; and (4) the institutional architecture of ethical Islamic economic practice, including zakat, waqf, and profit-and-loss sharing mechanisms. The study concludes that Islamic economics provides a substantively coherent and practically relevant ethical framework that addresses foundational deficiencies of conventional development models, while identifying key challenges in operationalization, institutional reform, and empirical substantiation that must be addressed to realize its transformative potential.